Goldeneye feeding close to sewer outfalls in winter - Campbell, L H; Milne, H (Wildfowl, 1977)
No diurnal or tidal patterns in feeding intensity of a flock of Goldeneye Bucephala clangula were detected. However, the birds concentrate at dawn and dusk close to a food factory sewer outlet where they feed on discharged vegetable waste. It is argued that the birds were exploiting a locally concentrated food source which enabled rapid food intake prior to or following the roost period. Such feeding could be of greater importance in severe weather.